Low number of neurosecretory vesicles in neuroblastoma impairs massive catecholamine release and prevents hypertension - Mühlethaler-Mottet, Annick; Uccella, Silvia; Marchiori, Deborah; La Rosa, Stefano; Daraspe, Jean; Balmas Bourloud, Katia; Beck Popovic, Maja; Eugster, Philippe J.; Grouzmann, Eric; Abid, Karim (Frontiers in Endocrinology, 2022)
Neuroblastoma (NB) is a pediatric cancer of the developing sympathetic nervous system. It produces and releases metanephrines, which are used as biomarkers for diagnosis in plasma and urine. However, plasma catecholamine concentrations remain generally normal in children with NB. Thus, unlike pheochromocytoma and paraganglioma (PHEO/PGL), two other non-epithelial neuroendocrine tumors, hypertension is not part of the usual clinical picture of patients with NB. This suggests that the mode of production and secretion of catecholamines and metanephrines in NB is different from that in PHEO/PGL, but little is known about these discrepancies. Here we provide a detailed comparison of the biosynthesis, metabolism and storage of catecholamines and metanephrines between patients with NB and PHEO. Plasma levels of metanephrines were comparable between NB and PHEO patients, while catecholamines were 3.5-fold lower in NB vs PHEO affected individuals. However, we observed that intratumoral concentrations of metanephrines and catecholamines measured in NB were several orders of magnitude lower than in PHEO. Cellular and molecular analyses revealed that NB cell lines, primary cells dissociated from human tumor biopsies as well as cells from patient-derived xenograft tumors (NB-PDX) stored a very low amount of intracellular catecholamines, and contained only rare neurosecretory vesicles relative to PHEO cells. In addition, primary NB expressed reduced levels of numerous chromaffin markers, as compared to PHEO/PGL, except catechol O-methyltransferase and monoamine oxidase A. Furthermore, functional assays through induction of chromaffin differentiation of the IMR32 NB cell line with Bt2cAMP led to an increase of neurosecretory vesicles able to secrete CATs after KCl or nicotine stimulation. Thus, the low amount of neurosecretory vesicles in NB cytoplasm prevents catecholamine storage and lead to their rapid transformation by catechol O-methyltransferase into metanephrines that diffuse in blood. Hence, in contrast to PHEO/PGL, CATs are not secreted massively in the blood, which explains why systemic hypertension is not observed in most patients with NB.